MODEL BISNIS TOKO JAMU KARYA SUBUR - Rossiana Cendra Kasih; Hadi Ismanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This research aims to analyze the business model of the Jamu Karya Subur Shop using the Business Model Canvas (BMC) approach. Toko Jamu Karya Subur is a micro and small industry operating in the field of traditional herbal medicine, which has been operating since 2002. This research is motivated by the challenges faced by Toko Jamu Karya Subur, such as limited reach of information to customers and low competitiveness in the digital era. The research method used is qualitative phenomenological, which aims to understand the subjective experiences of owners and customers. Data collection was carried out through interviews, observation and documentation. Research subjects consisted of shop owners, franchise partners and customers. The research results show that the Jamu Karya Subur Shop has great potential to develop, but there needs to be innovation in marketing strategy and product development. The analysis results show that key elements in BMC, such as key partners, channels and customer relationships, are the main focus in developing business models. Toko Jamu Karya Subur's key partners include suppliers of herbal raw materials and distribution partners who can help expand the marketing network. The channels currently used are still limited to word of mouth promotion, so it is necessary to develop digital marketing channels to reach wider customers. Apart from that, customer relationships need to be improved through better service and the use of social media as a means of communication with customers. This research makes a significant contribution to the development of the Jamu Karya Subur Shop business model and provides recommendations for other micro and small businesses to pay attention to innovation and marketing strategies in facing competition in the digital era. By implementing BMC, it is hoped that Jamu Karya Subur Shop can increase its competitiveness and expand the market, so that it can continue to contribute to the local economy.